The bully pulpit Theodore Roosevelt, William Howard Taft, and the Golden Age of journalism - Goodwin, Doris Kearns (New York Simon & Schuster, 2013)
Doris Kearns Goodwin, author of the acclaimed multi-million copy bestseller Team of Rivals: The Political Genius of Abraham Lincoln, now turns to the birth of America's Progressive Era - that heady, optimistic time when the 20th Century is fresh. Reform is in the air, and it is time to take on the robber barons and corrupt politicians who have brought the country to its knees.
Includes bibliographical references (pages 753-867) and index.
Keywords: Roosevelt, Theodore, 1858-1919.